Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1994
DOI: 10.1136/oem.51.5.357
|View full text |Cite
|
Sign up to set email alerts
|

The presence of 1-naphthol in the urine of industrial workers exposed to naphthalene.

Abstract: I-Naphthol at concentrations ranging from 0-4 to 34-6 mg/l was found in urine collected directly after the end of the work shift from a group of industrial workers employed in distillation of naphthalene oil. The maximum excretion was found one hour after the end of the shift and the mean excretion rate was 057 mglh. Coke plant workers exposed to naphthalene and other aromatic and polycyclic hydrocarbons also had 1-naphthol in their urine. Mean values were 0-89 mg/l (working with new technology) and 4-86 mg/l … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0
2

Year Published

1997
1997
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 6 publications
1
23
0
2
Order By: Relevance
“…In an earlier study it has been shown that there is a good statistical correlation between 1-naphthol excretion and naphthalene exposure in the concelltration range of 0.2-6 mg/m3. This urinary metabolite can indicate exposure to both naphthalene and low concentrations of 1-naphthol during the naphthalene oil distillation process (15). Our study confirms a previous assumption that there is a correlation between the presence of naphthalene in air and the urinary excretion of 1-naphthol and 2-naphthol, which are two major oxygenated metabolites of naphthalene.…”
Section: T T H I S S T U D Y S H O W S T H a T O P E R A T O R S Insupporting
confidence: 80%
See 2 more Smart Citations
“…In an earlier study it has been shown that there is a good statistical correlation between 1-naphthol excretion and naphthalene exposure in the concelltration range of 0.2-6 mg/m3. This urinary metabolite can indicate exposure to both naphthalene and low concentrations of 1-naphthol during the naphthalene oil distillation process (15). Our study confirms a previous assumption that there is a correlation between the presence of naphthalene in air and the urinary excretion of 1-naphthol and 2-naphthol, which are two major oxygenated metabolites of naphthalene.…”
Section: T T H I S S T U D Y S H O W S T H a T O P E R A T O R S Insupporting
confidence: 80%
“…Investigations by Connor et a1 (28) have shown that smoking can contribute to the excretion of 1-naphthol in urine. Recent studies have demonstrated that the maximum concentration of 1-naphthol in the urine of operators working with the naphthalene oil distillation process appears 1 h after the end of a shift (15). The 1-naphthol concentration was the highest in the morning before the workday.…”
Section: T T H I S S T U D Y S H O W S T H a T O P E R A T O R S Inmentioning
confidence: 99%
See 1 more Smart Citation
“…A small number of studies have reported the elimination kinetics of urinary PAH biomarkers other than 1-PYR. The t 1/2 for 1-NAP was 4 h in workers conducting naphthalene oil distillation, 35 and 1.2-1.9 h and14-46 h (two-phase excretion) in 2 smoking workers. 36 Sobus et al collected pre-, post-shift, bedtime and morning samples from 20 asphalt pavers; the calculated half-lives were 26 h (95% CI: 14−116 h) for naphthols (summation of 1-NAP and 2-NAP) and 14 h (9.0-28 h) for phenanthrols (summation of 1-, 2-, 3-, 4-and 9-PHE).…”
Section: Excretion Kinetics and Half-life Estimatesmentioning
confidence: 99%
“…Although primarily associated with carbaryl elimination, urinary 1-naphthol is also attributed to naphthalene exposure, especially from cigarette smoke (14,15).…”
Section: Resultsmentioning
confidence: 99%